Genetic diversity of hantaviruses in Mexico: Identification of three novel hantaviruses from Neotominae rodents - Kariwa, Hiroaki; Yoshida, Haruka; Sánchez-Hernández, Cornelio; Romero-Almaraz, María de Lourdes; Almazán-Catalán, José Alberto; Ramos, Celso; Miyashita, Daisuke; Seto, Takahiro; Takano, Ayako; Totani, Masashi; Murata, Ryo; Saasa, Ngonda; et al. (Virus research, 2012)
► Three novel hantaviruses were identified from Mexican Neotominae rodents. ► Newly identified Mexican viruses were designated Montano, Carrizal, and Huitzilac. ► Mexican viruses were closely related with Limestone Canyon or El Moro Canyon viruses. ► Mexican viruses were distant from Playa de Oro virus previously identified in Mexico. A variety of hantaviruses are harbored by rodents in North and South America, some of which can cause hantavirus pulmonary syndrome. To obtain greater evolutionary insight into hantaviruses in the Americas, a total of 211 rodents were captured in the Mexican states of Guerrero and Morelos in 2006. Anti-hantavirus antibodies were detected in 27 of 211 serum samples (12.8%) by ELISA. The distribution of seropositive rodents was: 17 Peromyscus beatae, 1 Megadontomys thomasi, 1 Neotoma picta, 6 Reithrodontomys sumichrasti, and 2 Reithrodontomys megalotis. The hantavirus small (S), medium (M), and large (L) genome segments from P. beatae, R. sumichrasti, and R. megalotis were amplified and the sequences covering the open reading frames were determined. The hantaviruses from P. beatae, R. sumichrasti, and R. megalotis were provisionally designated Montano (MTN), Carrizal (CAR), and Huitzilac (HUI), respectively. The M segment amino acid identities among the Mexican hantaviruses were 80.8–93.0%. When these M segments were compared to those of known hantaviruses, MTN virus was most closely related to Limestone Canyon (LSC) virus (88.9% amino acid identity), while the CAR and HUI viruses were most closely related to El Moro Canyon (ELMC) virus (90–91% identity). Phylogenetic analysis revealed that the MTN, CAR, and HUI viruses occupy a monophyletic clade with the LSC, ELMC, and Rio Segundo viruses, which are harbored by Peromyscus boylii, R. megalotis, and Reithrodontomys mexicanus, respectively. The data obtained in this study provide important information for understanding the evolution of hantaviruses in the Americas.